2010
DOI: 10.1111/j.1463-1326.2010.01337.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of pramlintide acetate on glycemic control and weight in patients with type 2 diabetes mellitus and in obese patients without diabetes: a systematic review and meta-analysis

Abstract: pramlintide was associated with a small reduction in HbA1c, and a modest reduction in weight in patients with T2DM or OBP. There was increased incidence of nausea but not hypoglycaemia at any time during therapy. Studies about the long-term effect of pramlintide on diabetes- and cardiovascular-related complications and cost-effectiveness analyses are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 25 publications
1
51
0
Order By: Relevance
“…However, amylin remains effective at reducing food intake and body weight in the obese state (7). In fact, the amylin analog pramlintide is FDA approved for the treatment of diabetes but has the additional effect of reducing food intake and body weight in obese individuals (12,52,53). This finding, along with the ability of amylin receptor signaling to enhance the body weight-lowering effects of other neuroendocrine signals (22), has led to the notion that the amylin system is a strong candidate for future antiobesity drug development (30,47,51).…”
Section: Discussionmentioning
confidence: 99%
“…However, amylin remains effective at reducing food intake and body weight in the obese state (7). In fact, the amylin analog pramlintide is FDA approved for the treatment of diabetes but has the additional effect of reducing food intake and body weight in obese individuals (12,52,53). This finding, along with the ability of amylin receptor signaling to enhance the body weight-lowering effects of other neuroendocrine signals (22), has led to the notion that the amylin system is a strong candidate for future antiobesity drug development (30,47,51).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, in the extension to 1 year, the placebo group regained their baseline weight but the pramlintide-induced weight loss was durable. Meta-analysis of randomized clinical trials in obese patients supports a mild but statistically significant weight loss of just over 2 kg with pramlintide compared with placebo [80].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Numerous studies have been performed on obese patients with PCOS, who received metformin. While the irst studies seemed to demonstrate its efects in terms of weight loss, decreased serum androgen levels (and implicitly hirsutism), restoration of menstrual cycles, and induction of ovulation [54], further studies concluded its inefectiveness in treating hirsutism or increasing live birth rates, even if it is efective in increasing the ovulatory rates and pregnancy rates. Metformin is no longer used as a irst-line treatment for oligomenorrhea or weight loss.…”
Section: Diabetes Drugsmentioning
confidence: 99%